Investigation of excipients’ nature influence on the quality indices of effervescent tablets of acetylsalicylic acid, paracetamol and ascorbic acid - О. V. Tryhubchak; Т. А. Groshovyi; S. N. Gureeva (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The priority objective of pharmaceutical science remains the creation and rational use of medicines. In recent years among these medicines particular attention is paid to the form of sparkling (fast-dissolving, gaseous or effervescent) solid dosage forms – tablets, granules, powders, microspheres, capsules, suppositories and others. In the development of effervescent tablets, which are absent in the domestic market, a combination of acetylsalicylic acid, paracetamol and ascorbic acid was selected for experimental studies.